Quality of life of patients after implantation of a pacemaker - Kamil Sikora; Agnieszka Wawryniuk; Robert Jan Łuczyk; Marta Łuczyk; Agnieszka Zwolak; Wiesław Fidecki; Mariusz Wysokiński (Kazimierz Wielki University, 2020)
Introduction. According to data from 2017 provided by the National Health Fund, nearly 30,000 pacemakers and 10,000 cardioverter-defibrillators have been implanted in Poland so far. Pacemaker implantation alone results in an improvement in the quality of life in approximately 35% of patients. Interest in the subject of quality of life can be seen in researchers from various fields since the middle of the last century. Despite the passing years, the demand for comprehensive research on the quality of life in the group of patients with an implanted pacemaker does not decrease. Purpose of research. The aim of the study was to assess the quality of life of patients after implantation of a pacemaker. Material and methods. The study included 100 patients after implantation of a pacemaker, treated at the SPSK 4 cardiology ward and outpatient clinic in Lublin from January to May 2020. The diagnostic survey method was used, and the WHOQOL-BREF standardized tool was used to collect the research material. The obtained results were compiled in a statistical analysis. Results. It was shown that 64% of patients with implanted pacemakers rated their quality of life as at least good. The result of the self-assessment of health was lower, 41% of respondents scored above the average criterion. The highest results were observed in the domain of the functioning environment, and the lowest in the physical domain. Conclusions. The quality of life of most subjects with an implanted pacemaker is at least at a good level. Self-assessment of patients' health is lower than the overall assessment of the quality of life. In patients with an implanted pacemaker, the quality of life was rated the lowest in the physical domain, and the highest in the aspect of the functioning environment.